2016
DOI: 10.2134/jeq2015.07.0397
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Properties of Biochar Produced from Simulated Human Feces and Its Potential Applications

Abstract: This study presents a comprehensive characterization of biochar obtained from simulated human feces (SHF) with a view to improve human waste sanitization and stabilization before usage as a resource. The possible applications of SHF are as a fuel, as a soil amendment, or for emerging applications (e.g., activated carbon precursor and odor control), depending on the charring conditions. Simulated human feces were charred under different conditions of peak temperature (200-800°C), heating rate (2-50°C min), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…3−5 Technologies for N removal from wastewater can help reduce environmental contamination while promoting recovery of fertilizer nutrients as soil amendments. 6,7 Zeolites, ion-exchange resins, and activated carbon have been investigated to trap plant-available N species such as ammonium (NH 4 + ) and nitrate (NO 3 − ) from liquid streams. 8−15 Ammonia gas (NH 3 ) is another concern due to its high toxicity, with point-source pollution arising from fertilizer, 16,17 animal production, 18 and composting.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3−5 Technologies for N removal from wastewater can help reduce environmental contamination while promoting recovery of fertilizer nutrients as soil amendments. 6,7 Zeolites, ion-exchange resins, and activated carbon have been investigated to trap plant-available N species such as ammonium (NH 4 + ) and nitrate (NO 3 − ) from liquid streams. 8−15 Ammonia gas (NH 3 ) is another concern due to its high toxicity, with point-source pollution arising from fertilizer, 16,17 animal production, 18 and composting.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In communities lacking sewerage, indiscriminate disposal of nutrient-enriched liquids and pathogen-laden solid wastes poses environmental and sanitation hazards. , At the same time, between 70 and 90% of waste nitrogen (N) is excreted in the urine in the form of urea (CH 4 N 2 O), a commonly applied N fertilizer worldwide. Technologies for N removal from wastewater can help reduce environmental contamination while promoting recovery of fertilizer nutrients as soil amendments. , …”
Section: Introductionmentioning
confidence: 99%
“…Due to its abundant macronutrients, pyrolyzed fecal biochar also has great potential as a tree substrate component that replaces mineral fertilizers and closes nutrient cycles using natural recycled products, as shown in Fig. 1 (Bleuler et al, 2020;Ilango and Lefebvre, 2016). However, while much research is available on the effect of biochar from plant biomass, there are few studies on the use of fecal biochar from animal or human excreta.…”
Section: Introductionmentioning
confidence: 99%
“…The use of fecal biochar has not been extensively researched and it is rarely used in practice, probably due to the fear of diseases and heavy metals that may be present in the fecal matter (Bleuler et al, 2020;Ilango and Lefebvre, 2016). However, studies by Ebert et al (2021), Bleuler et al (2020) and Gold et al (2017) indicated that the heavy metal content of fecal biochar is even lower than in previously studied sewage sludge-based biochar.…”
Section: Introductionmentioning
confidence: 99%
“…Biochar is a carbon‐rich residue produced from the thermal decomposition of a large number of types of feedstock, including crop residues, sewage sludge as well as manure under oxygen limited condition. Great interest has been shown for both agricultural and environmental purposes due to its unique physicochemical properties, such as highly heterogeneous composition and high organic carbon content .…”
Section: Introductionmentioning
confidence: 99%